The English Emblem Tradition/Emblematica - Moseley, C.W.R.D. (Modern Language Review, 2001)
Reviews the books 'The English Emblem Tradition,' Volume IV, edited by Peter M. Daly with Leslie T. Duer and Mary V. Silcox and Volume V, edited by Alan R. Young with Beert Verstraete and 'Emblematica: An Interdisciplinary Journal for Emblem Studies,' edited by Peter M. Daly, Daniel S. Russel and John Manning.